Pattern Recognition and Machine Learning Approach for Stock Trading Decisions: A Review - Nayak, Sonalika; Mantri, Jibendu Kumar; Swain, Prasanta Kumar (International Journal of Computer Sciences and Engineering, 2023)
Stock Trading Decisions are important in selection of the right stock at the right time. There are traditional and regular methods for identifying superior stocks for investment but looking into volatility of current market scenario, new technologies must be incorporate to accomplish the target. Here, we presented a review on use of pattern recognition approach and machine learning techniques for Stock Trading Decisions. Usually common patterns are seen in the buying and selling data of stocks for a specific business house. Analysing these data patterns with the use of machine learning approach will produce a better result for Trading Decision. Different machine learning models has been built and applied by different authors to achieve better stock trading decisions.